2021
DOI: 10.48550/arxiv.2111.04301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transition from a polaronic condensate to a degenerate Fermi gas of heteronuclear molecules

Abstract: The interplay of quantum statistics and interactions in atomic Bose-Fermi mixtures leads to a phase diagram markedly different from pure fermionic or bosonic systems. However, investigating this phase diagram remains challenging when bosons condense. Here, we observe evidence for a quantum phase transition from a polaronic to a molecular phase in a density-matched degenerate Bose-Fermi mixture. The condensate fraction, representing the order parameter of the transition, is depleted by interactions and the buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 57 publications
(99 reference statements)
0
23
0
Order By: Relevance
“…Both methods utilize fields, either optical or slowly-varying magnetic, to couple atomic scattering states to bound molecular states, in either excited or ground electronic potentials. Since the associated molecules inherit the phase-space density of its atomic constituents, molecular gases created this way hold the record for the highest phase-space densities to date [27][28][29][30][31]. Three decades of progress in laser cooling and trapping of atoms have now enabled single diatomic molecules to be assembled atom-by-atom in the ground motional state of an optical tweezer (Fig.…”
Section: Molecule Assembly and Sympathetic Coolingmentioning
confidence: 99%
“…Both methods utilize fields, either optical or slowly-varying magnetic, to couple atomic scattering states to bound molecular states, in either excited or ground electronic potentials. Since the associated molecules inherit the phase-space density of its atomic constituents, molecular gases created this way hold the record for the highest phase-space densities to date [27][28][29][30][31]. Three decades of progress in laser cooling and trapping of atoms have now enabled single diatomic molecules to be assembled atom-by-atom in the ground motional state of an optical tweezer (Fig.…”
Section: Molecule Assembly and Sympathetic Coolingmentioning
confidence: 99%
“…The surprisingly strong suppression of dimer-dimer loss in the non-halo regime suggests that after molecule formation, dimer loss can be strongly reduced by quenching the magnetic field into the regime of large binding energies. This has, for example, been essential in our recent work on the generation of degenerate Fermi gases of NaK molecules [29,30].…”
mentioning
confidence: 99%
“…Typically, numbers have ranged from 1,000 to 20,000 molecules and temperatures from 200 to 1200 nK. Recently, it has been shown that degenerate Fermi gases of KRb [29] and NaK [30] can be directly created through optimized Feshbach association from the initial Bose-Fermi mixture, reaching temperatures of 50 nK and 100 nK, respectively. The equivalent for heteronuclear bosonic molecules, the creation of a molecular BEC, has not been achieved yet.…”
mentioning
confidence: 99%